Characterization and Thermodynamics of a Natural Mineral Dye-Based Chromium Complex Dye on Cotton Fabric - Adebayo, G.B.; Orimolade, B.O.; Adegoke, H.I.; Saliu, O.D.; Ajetomobi, O.O. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2019)
Transition metal complex of a bisazo dye derived from p-phenylenediamine extracted from a natural mineral dyeand p-nitroaniline was synthesized with the azo dye acting as ligand for the metal complex dye. The ligand, azo dyeand the metal complex were characterized using UV-visible spectroscopy, IR spectroscopy and GC-MS. The IRspectroscopy of both the ligand and the complex reveal the presence of azo group (N=N) at 1597 cm-1, N-O at 1384cm-1 and other Metal-Ligand (M-L) bonds at 418 cm-1. The results were used to establish the type of metal complexformed to be 1:1 (metal: ligand) and possible structure of the complex was proposed. The metal complex dye wasapplied on cotton fabric and the thermodynamics parameters of the dyeing process were determined. Theseparameters included the enthalpy change which was -58.94 KJmol-1 and the entropy which was 0.159 KJmol-1. Thethermodynamics studies of the dye showed that the dye has high substantivity and fastness that can be useful indyeing fabric.